Contemporary management of severe symptomatic bicuspid aortic valve stenosis: the BiTri Registry. Issue 6 (June 2021) - De Biase, Chiara; Siddiqui, Saif; Brochado, Bruno; Ziviello, Francesca; van Mieghem, Nicolas M.; De Backer, Ole; Sondergaard, Lars; Silveira, João; Saint-Etienne, Christophe; Bourguignon, Thierry; Lange, Rudiger; Jovanovic, Marija; et al.
Abstract : Aims: A greater number of patients with bicuspid aortic valves (BAV) may be identified and treated as indications for transcatheter aortic valve implantation (TAVI) are expected to expand to younger patients. We evaluated the contemporary frequency and management of symptomatic patients with stenotic BAV in a multicenter European registry. Methods: Between November 2017 and February 2018, all consecutive patients admitted for symptomatic aortic stenosis across six high-volume European hospitals were prospectively enrolled in the BiTri registry. Results: Of the 832 patients, 17% ( n = 138) had a BAV. The most frequent BAV phenotypes were type 1 (left--right coronary cusps fusion 64%) and type 1 (right-noncoronary cusps fusion 17%). Type 0 and type 2 accounted for 12 and 2%, respectively. When compared with tricuspid patients ( n  = 694), BAV patients were younger, with lower surgical risk. The transthoracic echocardiography (TTE) identified BAV in 64% of patients. Multisliced computed tomography (MSCT) additionally completed the diagnosis in 20% of patients. Surgical inspection finally identified the remaining undiagnosed 16% of BAV. A combination of TTE and MSCT was the most common diagnosis method for BAV. Surgical aortic valve replacement (SAVR) was the predominant therapeutic option for BAV (70%) whilst TAVI was performed in 26%. Conclusion: BAV is frequently observed in symptomatic patients with aortic stenosis. These patients are younger, have a lower risk profile and are predominantly treated with SAVR as compared with tricuspid patients. However, TAVI is performed in almost one-third of BAV patients in contemporary European practice. TTE combined with MSCT identified 84% of BAV. Abstract : Supplemental Digital Content is available in the text